2009
DOI: 10.1177/1403494809354361
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work environment and intention to leave the nursing profession: Results from the longitudinal Chinese NEXT study

Abstract: The findings suggest that unfavourable psychosocial work environment predicts ITL in Chinese nurses. Improvements in the psychosocial work environment may be helpful in retention of the nursing workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 24 publications
6
74
0
Order By: Relevance
“…Items on psychosocial working conditions were from the Copenhagen Psychosocial Questionnaire (COPSOQ I), developed as a valid and reliable comprehensive tool for assessing psychosocial working environment; it has been used in many work-related health studies among different job group and health care workers [26,27]. Six subscales of the COPSOQ I questionnaire were chosen to measure psychosocial working conditions.…”
Section: Questionnairementioning
confidence: 99%
“…Items on psychosocial working conditions were from the Copenhagen Psychosocial Questionnaire (COPSOQ I), developed as a valid and reliable comprehensive tool for assessing psychosocial working environment; it has been used in many work-related health studies among different job group and health care workers [26,27]. Six subscales of the COPSOQ I questionnaire were chosen to measure psychosocial working conditions.…”
Section: Questionnairementioning
confidence: 99%
“…In studies of absence, burnout, exclusion from the labour market, and return to work, the following significant independent risk factors have been identified: Meaning of work [10][11][12][13], predictability [10,11,13,14], quality of leadership [10,11,15], role conflicts [10,11,15], and emotional demands [10,15]. Seen across these studies [10][11][12][13][14][15] and the results reported in this issue [4][5][6][7][8][9], it is remarkable to see the high number of studies showing significant associations with emotional demands, meaning of work, and predictability. This is not the place to elaborate further on this strong pattern, but our results clearly deserve theoretical consideration and discussion.…”
Section: The Aims Of Copsoqmentioning
confidence: 99%
“…The results from a study in 2010 indicated that high emotional demands, low meaning of work, low commitment to the workplace, and low job satisfaction were constantly predictive factors for nurses intending to leave their job (37). In a study among the European nurses, the three most important factors strongly associated with nurses' intention to leave were poor professional opportunities, unpleasant work organization, and low health status (38).…”
Section: Discussionmentioning
confidence: 99%